2007
DOI: 10.1016/j.neuroimage.2007.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Age of acquisition modulates neural activity for both regular and irregular syntactic functions

Abstract: Studies have found that neural activity is greater for irregular grammatical items than regular items. Findings with monolingual Spanish speakers have revealed a similar effect when making gender decisions for visually presented nouns. The current study extended previous studies by looking at the role of regularity in modulating differences in groups that differ in the age of acquisition of a language. Early and late learners of Spanish matched on measures of language proficiency were asked to make gender deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 79 publications
6
49
1
1
Order By: Relevance
“…English also . IFG activity seems to reflect varying levels of proficiency and/or age of acquisition rather than intrinsic differences between L1 and further languages: Increased activity of left IFG was also observed for words of the first language, which are learned later in life (Fiebach et al 2003) and for late learners of a second language in comparison to early learners (Hernandez et al 2007). As age of language acquisition, language exposure and proficiency are correlated (Indefrey 2006), it is difficult to differentiate between these variables.…”
Section: Brain Activity Related To Low Language Proficiencymentioning
confidence: 99%
“…English also . IFG activity seems to reflect varying levels of proficiency and/or age of acquisition rather than intrinsic differences between L1 and further languages: Increased activity of left IFG was also observed for words of the first language, which are learned later in life (Fiebach et al 2003) and for late learners of a second language in comparison to early learners (Hernandez et al 2007). As age of language acquisition, language exposure and proficiency are correlated (Indefrey 2006), it is difficult to differentiate between these variables.…”
Section: Brain Activity Related To Low Language Proficiencymentioning
confidence: 99%
“…So far, many studies have investigated brain activities of bilinguals involved in the processing of L1 and L2, and as summarized by Indefrey (2006) and Abutalebi (2008), differences between L1 and L2 are usually reflected at the brain level by more extended activation patterns of L2 within or surrounding those regions responsible for L1 processing. As to why L2 engages more widespread brain activity, several studies have also suggested that the brain activity for language processing is modulated by specific demographic, linguistic and/or behavioral variables, such as language exposure in daily life Jeong et al, 2007;Perani et al, 2003), proficiency level (PL) (Briellmann et al, 2004;Chee, Caplan, et al, 1999;Frenck-Mestre, Anton, Roth, Vaid, & Viallet, 2005;Gandour et al, 2007;Golestani et al, 2006;Illes et al, 1999;Kotz, 2009;Perani et al, 1996Perani et al, , 1998, age-of-acquisition (AoA) of L2 (Bloch et al, 2009;Dehaene et al, 1997;Hernandez, Hofmann, & Kotz, 2007;Kim, Relkin, Lee, & Hirsch, 1997;Mayberry, Chen, Witcher, & Klein, 2011;Perani et al, 2003;Wartenburger et al, 2003), cross-linguistic similarities/dissimilarities (Jeong et al, 2007;Saur et al, 2009), and syntactic complexity (Suh et al, 2007;Yokoyama et al, 2006). Following Abutalebi and Green (2007), the extra-activity of L2 would be induced by an apparent lack of automaticity such as in cases where the proficiency for L2 is low or, likewise, when L2 is learnt later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Such processing involves syntactic information at the word level, for example, word-category information or syntactic gender Heim et al, 2003;Hernandez et al, 2007;Longoni et al, 2005]. Furthermore, Broca's region is involved in integrating these types of information into syntactically complex structures [e.g.…”
Section: Introductionmentioning
confidence: 99%